Historical linguistics and Biblical Hebrew : an Indo-Europeanist’s view - Klein, Jared S. (Journal for semitics, 2016)
Rezetko and Young’s Historical linguistics and Biblical Hebrew: steps toward an integrated approach brings variation analysis to bear on the question of the periodisation of Biblical Hebrew. However, this methodology is at best microdiachronic, dealing with variation in synchronic terms. In order to answer the question they pose, a language with a history as long as Biblical Hebrew requires macrodiachronic techniques which look at real linguistic processes. Several such processes are discussed in this paper, and though they collectively converge in pointing to a late date for Qoheleth, they are insufficient to establish a linguistically-based entity "Late Biblical Hebrew". At the present time, one can at best apply this term in a non-linguistic sense to the Hebrew of those books known on extra-linguistic grounds to have been chronologically late.